Pengujian Empiris Brand Satisfaction terhadap Brand Loyalty yang di Moderasi oleh Emotional Brand Attachment dan Brand Love - Irfan Hajjid; Harsini Soetomo; Robert Kristaung; Agus Susanto (STIE-JIC, 2022)
This research aims to test for emotional brand attachment and brand love as a mediator of brand satisfaction on brand loyalty. The purposive sampling technique was used to select 150 active users of Samsung smartphones. Furthermore, the data were collected by distributing questionnaires using Google Form, and the hypothesis testing used the Structural Equation Modeling (SEM). The results showed brand satisfaction has a positive effect on emotional brand attachment and brand loyalty. Likewise, satisfaction on emotional brand attachment and brand love has a positive effect on brand loyalty. There was a partial mediating role of emotional brand attachment and brand love between brand satisfaction and brand loyalty. The implication is that brand loyalty will be stronger with emotional brand attachment and feelings of love for the brand, hence, the more loyal consumers will continue patronage. Subsequent studies can refine this research model by adding variables that affect brand satisfaction, namely perceived quality, perceived cost value, trust, and lifestyle congruence.